THE INFLUENCE OF SOCIAL CAPITAL AND ENTREPRENEURIAL ALERTNESS ON THE ENTREPRENEURIAL INTENTION OF ENTREPRENEURSHIP STUDY PROGRAM STUDENTS AT UNIVERSITAS PGRI SUMATERA BARAT: PENGARUH MODAL SOSIAL DAN ENTREPRENEURIAL ALERTNESS TERHADAP ENTREPRENEURIAL INTENTION MAHASISWA PROGRAM STUDI KEWIRAUSAHAAN UNIVERSITAS PGRI SUMATERA BARAT - Muhammad Tsabit; Yuhendri LV (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
Someone who wants to become an entrepreneur must have entrepreneurial intentions. This entrepreneurial intention is still a problem in the entrepreneurship study program at Universitas PGRI Sumatera Barat. The purpose of this study was to analyze the effect of social capital and entrepreneurial alertness on entrepreneurial intentions in entrepreneurship study program students at Universitas PGRI Sumatera Barat, analyze the effect of social capital on entrepreneurial intentions in entrepreneurship study program students at Universitas PGRI Sumatera Barat, and analyze the effect of entrepreneurial alertness on entrepreneurial intentions in entrepreneurship study program students at Universitas PGRI Sumatera Barat. This study uses a quantitative approach with a causative type. Sampling in this study using total sampling technique. The research instrument of this study used a questionnaire. The data analysis technique of this research is multiple linear regression analysis. The results showed that together there is a significant influence between Social Capital, and Entrepreneurial Alertness on entrepreneurial intentions of Entrepreneurship Study Program Students of Universitas PGRI Sumatera Barat, Social Capital has no significant effect on entrepreneurial intentions in Entrepreneurship Study Program students of Universitas PGRI Sumatera Barat, and Entrepreneurial Alertness has a significant influence on entrepreneurial intentions in Entrepreneurship Study Program students of Universitas PGRI Sumatera Barat. This study concludes that to increase entrepreneurial intention requires an increase in entrepreneurial alertness.